Desenvolvimento sustentável na agricultura familiar: um estudo com base nos indicadores sociais, econômicos e ambientais - Viganó, Caroline (2020)
The general objective of this study was to select and build sustainable development indicators (DS) in dairy family farming (AF), in order to assess the multidimensional processes and practices of sustainability. The specific objectives were: a) To build and propose DS indicators in AF in order to assess the social, economic and environmental dimensions; b) Carry out the survey and evaluation of DS indicators of dairy AFs. The theoretical approaches used to carry out the research include sustainable and rural sustainable development, family farming and sustainability indicators. The elaboration of this work took place from a field research carried out in 10 productive units of family farmers of dairy cattle, in the Passo da Ilha Community, in the Municipality of Pato Branco/PR. To make the sustainabilityassessment operational, 79 indicators were identified in the literature through a bibliographic search. Of these, 31 indicators were selected and proposed in the three dimensions of the DS of AF (economic, social and environmental). The data were collected through the application of a questionnaire, semi-structured interview, photographs, observations and field diary, which were analyzed quantitatively and qualitatively. The main results obtained show that the DS of the investigated experiences correspondsto an average level of sustainability with a score of 2.4, on a scale of 1 to 4. The most fragile indicators are the economic gains in the marketing channels, added value of production, basic sanitation practices and the intention to continue UP activities, which presented the lowest scores. The indicators with the best results are the annual gross income per capita, the quality of housing for farmers and the sustainable practices of production units. It should be noted that the study of the indicators must be carried out from the outside to integrate them in the analyzes carried out and the ideal would be to maintain evaluations and monitor them over time to make corrections and improvements to the weak indicators. SD indicators are important planning tools for regional social actors and their constant monitoring and evaluation can provide valuable subsidies for institutions and public policies that aim at sustainable development in family farming.